UNPERCEIVED CIVIL RELIGION IN SCIENCE. - Kasak, Enn (Problems / Problemos, 2011)
The concept of civil religion, as used in social philosophy, can also be applied in the study of science in a slightly different way, as we can find unperceived religious attitudes in trusting beliefs and feelings of sanctity among scientists. Such reactions evoke the use of questionable argumentation in the struggle against pseudo-sciences, spawning contextual demagogy in scientific propaganda. Recognising civil religion in science enables us to distinguish disciplines in which religiosity is a misleading phenomenon (e.g. physics) from others that are based on religious convictions (e.g. astrology). Religiosity in science can be analysed via multidimensional scales of religiosity. Using pragmatist ideology, scientists could retain their devotion to cognizing reality without deviating into civil religion.